Understanding the Emergence of Public Debt - Martin Fochmann; Abdolkarim Sadrieh; Joachim Weimann (Center for Economic Studies and ifo Institute (CESifo), 2014)
We use a controlled laboratory experiment with and without overlapping generations to study the emergence of public debt. Public debt is chosen by popular vote, pays for public goods, and is repaid with general taxes. With a single generation, public debt is accumulated prudently, never leading to over-indebtedness. With multiple generations, public debt is accumulated rapidly as soon as the burden of debt and the risk of over-indebtedness can be shifted to future generations. Debt ceiling mechanisms do not mitigate the debt problem. With overlapping generations, political debt cycles emerge, oscillating with the age of the majority of voters.
Keywords: C92; H41; H63; 330; public debt and taxation; government spending; budget deficit; balanced budget; common pool resources